Association of Vitamin D Gene Receptor Polymorphism with Osteoporosis in Postmenopausal Women (Molecular Medicine Communications, 2023)
Osteoporosis is a critical and complicated systemic musculoskeletal disorder that encompasses low bone density (LBD) and weakening of osseous tissue at a microarchitectural level. This predisposes to increased bone fragility and subsequent risk of fractures. It is frequently encountered in postmenopausal women and has also been seen in elderly men. Vitamin D synchronizes bone and calcium homeostasis in the body by modifying the transcription of target genes through the Vitamin D receptor (VDR) and thus aids calcium uptake and bone-forming proteins. The main objective of the present research was to study the relationship of single nucleotide polymorphisms (SNP) (rs1544410 G>A) of the VDR gene with postmenopausal women who have osteoporosis in a Pakistani cohort. A total of 100 postmenopausal women, 50 without osteoporosis to be in the control group, and 50 with osteoporosis as cases, were enrolled in this study. The patients had no immediate family connections with each other. All the patients underwent BMD measurements at the lumbar spine and femoral neck by dual-energy X-ray absorptiometry scan for their diagnosis of osteoporosis based on World Health Organization (WHO) criteria (T score < -2.5 SD). A total of 25 participants had at least one allele of rs1544410, of which 14 were cases and 11 controls. The number of heterozygous and homozygous were present with similar ratios in both groups (p=0.973).  Age was noted to be correlated with osteoporosis (OR: 1.06; 95%CI: 1.004-1.12), (P
Keywords: Osteoporosis; single nucleotide polymorphism; vitamin D receptor; bone mineral density